Cultural geography of the archipelagos of fuego-patagonia during recent times. mobility and planning Geografía cultural de los archipiélagos de fuego-patagonia en tiempos recientes. movilidad y planificación - Borrero, Luis Alberto; Morello Repetto, Flavia; San Roman Bontes, Manuel Julio (My University, 2020)
The systematization of the concept of cultural geography and its usefulness in hierarchizing space according to cultural values and knowledge that have archaeological visibility and obstrusiveness, are reviewed. They consider the dynamics of mobility and human circulation in the Fuegian landscapes of the austral region, evaluating its variation under different conditions. The work aims to transcend the ethnic boundaries recognized by historical observations and ethnographic studies, focuses on recent times and, also, it is integrated with different approaches and concepts of specialized fields within the archaeological record, archaeozoology or studies of techno-economic systems, among others.
Keywords: adaptación; adaptation; archaeology; arqueología; fuegian; fueguino; hunter-gatherers organization; mobility; movilidad; organización cazadores-recolectores; patagonia; patagonia; planificación; planning